2008
DOI: 10.1099/vir.0.2008/000711-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HLA-A*01- and HLA-A*02-restricted CD8+ T-cell epitopes shared among group B enteroviruses

Abstract: Acute enteroviral infections ranging from meningitis, pancreatitis to myocarditis are common and normally well controlled by the host immune system comprising virus-specific CD8 + cytotoxic T lymphocytes (CTL). However, in some patients enteroviruses and especially coxsackieviruses of group B are capable of inducing severe chronic forms of diseases such as chronic myocarditis. Currently, it is not known whether divergences in the CTL-related immune response may contribute to the different outcome and course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…16,46 These data suggest that epitopes from the P3D region may be more effective, which is in accordance with recent findings in human beings. 47 In conclusion, the present study substantiates the impact of type I IFN in the prevention of severe acute and consecutively chronic myocarditis in mice. The primary identification of CVB3 epitopes enabled novel findings with regard to the activity and function of myocardial IP in acute myocarditis.…”
Section: Discussionsupporting
confidence: 63%
“…16,46 These data suggest that epitopes from the P3D region may be more effective, which is in accordance with recent findings in human beings. 47 In conclusion, the present study substantiates the impact of type I IFN in the prevention of severe acute and consecutively chronic myocarditis in mice. The primary identification of CVB3 epitopes enabled novel findings with regard to the activity and function of myocardial IP in acute myocarditis.…”
Section: Discussionsupporting
confidence: 63%
“…In the case of CV-B4, epitopes in the structural and 2C proteins have previously been mapped using CD4 + T-cell lines (Marttila et al, 2001(Marttila et al, , 2002, whilst the HLA class I-restricted CD8 + epitopes have been mapped in the 3C and 3D proteins of CV-B3 (Weinzierl et al, 2008). The latter study identified four CD8…”
Section: Discussionmentioning
confidence: 95%
“…It is well-established that only a fraction of CTL-epi- topes predicted by HLA binding algorithms are in fact recognized by virus specific CD8+ T cells [21]. Herein, we used a peptide binding assay based on UV-induced ligand exchange to rapidly assess which peptides of the HAV polyprotein form true HLA ligands.…”
Section: Discussionmentioning
confidence: 99%